Introducing a Precision Soil Conservation Curriculum: A Pre- and Post-Evaluation - Paulsen, Thomas H.; Polush, Elena; Clark, Taylorann; Cruse, Richard (Journal of Agricultural Systems, Technology, and Management, 2017)
The need for sustainable agricultural practices will not only be satisfied by reaching traditional farmers, but by reaching to all populations regardless of their agricultural background. The lack of agricultural literacy in secondary agricultural education has also been a concern in recent years, spurring the development of relevant and up-to-date curricula. This study focused on the implementation of a precision soil conservation curriculum in high school agricultural education programs located on the impaired South Fork Watershed of the Iowa River in Iowa. Within this study's settings and context, the curriculum implementation effectiveness was measured by students' attitudes and content knowledge acquisition. Our curriculum implementation, overall, appeared to have been effective. However, we do acknowledge that the effectiveness of the curriculum implementation could be defined broadly or affected by many other variables. Therefore, we suggest collecting further student data after large scale implementation of the curriculum.